The Implementation of Treffinger Learning Model using Jelajah Alam Sekitar (JAS) Approach in Respiration System Subject to Improve High School Student's Critical Thinking - Kumalasari, Selvi; Kumalasari, Selvi; Marianti, Aditya (Journal of Biology Education, 2021)
Jelajah Alam Sekitar (JAS) approach on student's critical thinking skills in the respiratory system. This research conducted at SMA N 1 Ungaran in the even semester of the 2020/2021 school year. The research design was a pre-experimental type One-group pre-test-post-test design. The population was all students of class XI MIPA SMA N 1 Ungaran. The samples of this research were students of class XI MIPA 1, XI MIPA 2, and XI MIPA 3 who were taken by purposive random sampling technique. The result showed that the students' critical thinking skills, based on the N-gain test, the percentage of students who categorized medium to high criteria was 94.44%. The students who achieved classical completeness were 87.96%. The average percentage achievement of critical thinking skills indicators were 1) analyzes arguments of 91.66% is in a very good category, 2) considers reliable or not reliable sources of 90.75% is in the very good category, 3) induces and considering the result of induction of 80.83% is in a good category, 4) defines the problem and considering the definition of 90.80% is in the good category, and 5) determines an action of 92.00% is in the very good category. Students and teachers gave positive responses to Treffinger's learning model using the JAS approach. This research concludes is that the implementation of the Treffinger learning model using the JAS approach is proven to improve the critical thinking skills of high school students on the respiratory system subject. To an extent, the highest category was discovered in the indicators of determining action and the lowest category was found in the indicators of inducing and considering the results of induction